“Caracterización física, química y capacidad antioxidante del aceite de almorta (Lathyrus sativus)” - Calero Tigmasa, Jessica Adriana (2024)
The purpose this research project was to assess the chemical composition and antioxidant capacity from almorta oil (Lathyrus sativus). For optimizing the extraction process, it was implemented a response surface experimental design, what consisted 11 experimental runs with distinct extraction times (60 min, 90 min, 120 min) and vegetal material relations mixed with ethanol and chloroform (1 :4, 1:6, 1:8). The seeds chemical composition analysis revealed, what they contain a high percentage of nitrogen-free extract (47,65 %), protein (28,01 %), moisture (10,92 %). Further, it was found a fat percentage (1,72 %), fiber (9,38 %) and ash (2,32 %). The optimal extraction yield was 1,71 %, which was reached in a time 114 minutes with a ratio of 1:8 plant material and water, with a desirability 0,970. The experimental value was slightly higher, with a yield 1,73 %, indicating, which the experimental conditions exceeded the forecast and are very favorable for research. Chromatographic analyzes identified five compounds, being with linoleic acid (55,05 %) the most predominant. The total phenols quantification was 232.11 µmol Fe+2/g, through the FRAP method and 0,20 IC50 4 (mg/ml) through the ABTS method. The physical and chemical analyzes indicated a peroxide value 2,14 meqO2/Kg, iodine value 85,12, acidity (Oleic Acid) 0,15 % m/m, density 0.8412 g/mL, as well as also the squalene amount 2,11 %. The extracted oil was properly stored at 4 °C in an amber container in a dark and cool environment. Given its content, this oil presents great potential for diverse applications in the functional foods and cosmetics industry.